Growth of human basophil lines derived from chronic myelocytic leukaemia cells in vitro: ultrastructure and X-ray microanalysis studies. - Fishman, P (1985)
Mononuclear cells from the peripheral blood of patients with chronic myelocytic leukaemia were grown and expanded in liquid culture in the presence of Con A-conditioned medium. An accelerated development of cells of the basophilic lineage was observed and resulted in the appearance of 85% mature basophils after 14 days of incubation. Transmission electron microscopy of developing basophils showed changes in the nucleus and active granule formation in the cytoplasm. By scanning electron microscopy, the immature cells were relatively smooth in comparison with the mature basophils which showed membranous microvilli. The chemical content of the cells at different days of culture was detected by X-ray microanalysis. Immature cells were characterized by a high level of phosphorus with a low level of sulphur. As maturation progressed, the amount of phosphorus decreased, while the level of the sulphur increased, reaching its highest peak in the mature basophils. The different amount of sulphur found in the cells during the maturational process most probably represents the amount of heparin located in the cell granules. This finding may be useful for studying the influence of growth factors on the development and differentiation of human basophils.